2014
DOI: 10.3389/fimmu.2014.00292
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 Ligand (CpG Oligodeoxynucleotide) Induces CLL B-Cells to Differentiate into CD20+ Antibody-Secreting Cells

Abstract: B-cell chronic lymphocytic leukemia (CLL) is the most frequent adult leukemia in the Western world. It is a heterogeneous disease characterized by clonal proliferation and the accumulation of CD5+ mature B lymphocytes. However, the normal counterpart from which the latter cells arise has not yet been identified. CD27 expression and gene expression profiling data suggest that CLL cells are related to memory B-cells. In vitro, memory B-cells differentiate into plasma cells when stimulated with CpG oligodeoxynucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 59 publications
3
21
0
Order By: Relevance
“…The concept whereby malignant B-cells are induced to differentiate into a more mature, non-malignant or less malignant state is clinically plausible and can be a promising strategy as differentiation therapy in CLL [ 14 , 29 , 33 35 ]. To the best of our knowledge, the present report is the first to demonstrate the modulatory effects of differentiation on factors that have an important role in physiopathology of CLL, including LEF1, TCL1, ROR1, FMOD, TNFRSF13B , PI3K, BTK, p27, BCL2, BCLXL, PUMA and MCL1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The concept whereby malignant B-cells are induced to differentiate into a more mature, non-malignant or less malignant state is clinically plausible and can be a promising strategy as differentiation therapy in CLL [ 14 , 29 , 33 35 ]. To the best of our knowledge, the present report is the first to demonstrate the modulatory effects of differentiation on factors that have an important role in physiopathology of CLL, including LEF1, TCL1, ROR1, FMOD, TNFRSF13B , PI3K, BTK, p27, BCL2, BCLXL, PUMA and MCL1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to differentiation-dependent apoptosis, differentiation therapy in CLL could potentially be combined with other targeted therapies or immunotherapy [ 35 ]. Indeed, terminal differentiation confers exquisite apoptotic sensitivity to proteasome inhibitors, inhibitors of the ER stress-associated pathway (IRE1/XBP1) [ 59 , 60 ], inhibitors of HSP90 [ 61 ], BCL2, BCLxL (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that CLL B-cells can differentiate spontaneously into antibody-secreting plasma cells in vivo (9, 10) and in vitro , when exposed to various stimuli and can produce IgM, IgG, and IgA (11, 12). It is thus possible that the malignant plasma cells are differentiated or transformed CLL B-cells (hypothesis 1, H1) .…”
Section: Resultsmentioning
confidence: 99%